An instrumental analysis of the production of English Monophthongs by Malay speakers / Asmah Laili Mohd Yunus - Asmah Laili, Mohd Yunus (2017)
The aim of this research is to examine the production of English monophthongs produced by the 10 selected ESL primary school pupils and four female teachers in relation to vowel quality and vowel length based on an instrumental analysis of the vowels. The rationale for examining these pronunciation features of young Malay speakers and their teachers was to discover how pupils at an early learning stage produce English vowels, and to look at the extent to which this relates to their teachers’ production of English vowels. The first two research questions focus on the description of the vowels based on their acoustic properties. The third question examines whether the teacher and pupil participants produce English vowels similarly. The forth research question looked at how closely the vowels produced by the participants resemble those in Malay, the first language of the participants. Based on the Formant Frequency Model, the first (F1) and second formants frequencies (F2) were measured. In order to investigate length contrast between typical vowel pairs, vowel duration was measured and compared. The findings suggest that the participants (both teachers and pupils) did not discriminate between vowel pairs where vowel quality is concerned, and in fact, the results show that their vowels occupy the same vowel space seen in previous studies on Malaysian English. However, unlike the pupils, the teachers produced length contrast between short and long vowels. No significant differences were found between comparable English and Malay vowels for the teachers and pupils suggesting they were being produced similarly in both these languages.